Hubungan antara Kadar Hematokrit dengan Derajat Keparahan Stroke Iskemik Fase Akut pada Pasien di Unit Penyakit Saraf RSUD Dr. Moewardi - Hidayat, Agung Wahyu; Suroto, .; Utari, Siti (Nexus Kedokteran Klinik, 2013)
Background: Stroke is the main cause of morbidities andÂ  the third leading cause of death in the world, also promote the functional disorder of the patient. The increase of hematocrit level is one ofÂ  risk factor the occurrence of ischemic stroke, by increasing the viscosity and decreasing blood perfusion to the brain. National Institute of Health Stroke Scale (NIHSS) is a parameter used to measure the severity of acute ischemic stroke. This study was proposed to know correlation between hematocrit levels and severity of acute ischemic stroke patients in neurolog ward Dr. Moewardi Hospital. Methods: This was an observational study with cross sectional analytic approach. A total of 44 subjects were selected by purposive sampling, they were acute ischemic stroke patients in neurology ward Dr. Moewardi Hospital. Data were collected by direct interview, examined the patients with NIHSS score and from medical record to got the value of hematocrit. Data analysis used multiple logistic regression models and were processed with Statistical Product and Service Solutions(SPSS) 17.00 forWindows. Results: This study showed a positive correlation and statistically significant between hematocrit levels and severity of acute ischemic stroke patients (r = 0,408; p < 0,009) with moderate correlation strength. Multiple logistic regression analysis showed OR = 8,086; CI 95% 1,108 â 59,005; and p = 0,039. Confounding factor, e.g smoking, and blood sugar have been controlled. Conclusions: There is moderate correlation between hematocrit levels and severity of acute ischemic strokeÂ  patients in neurology ward Dr. Moewardi Hospital. Keywords:Hematocrit levels, Severity of acute ischemic stroke, NIHSS Â